(untitled) (EDUCATION IN THE 21ST CENTURY, 2024)
This article reflects on the fluid nature of insiders and outsiders in discourse communities, with particular relevance to teaching reading. A discourse community is characterized by its use of specific communicative rules to achieve common goals. Students who are not familiar with these rules often find it hard to understand the conversation, whereas students in the community know how to speak and what patterns of speech apply within this particular group. This study explores the way in which learners move from being an outsider to insider by understanding a community’s purpose, values and language. It also addresses the misconception that difficulty in understanding academic discourse stems from a lack of intelligence, rather than unfamiliarity with the community’s conventions. The novelty of the article is that it applies the insider-outsider discussion to the teaching of reading and emphasize the importance of understanding a community’s language, values and practices to improve comprehension. The research highlights the pedagogical implications of these dynamics and provides new insights by comparing discursive practices in non-academic versus academic discourse communities. It claims that difficulties in comprehension of specialized discourse are not an indication of a lack of intelligence but rather ignorance towards how accepted conventions have been set in place among this community. It emphasizes the importance of a structured approach to teaching reading, which includes providing context, scaffolding learning, encouraging active participation and dispelling misguided beliefs about the nature of academic discourse. Findings from the research showed that recognizing the process of becoming an insider and supporting learners through this transition can significantly improve students’ reading comprehension and engagement. This approach not only helps learners handle complex texts but also challenges the misconception that difficulty in understanding academic discourse reflects a personal failing, instead framing it as a natural part of the learning process.